Analysis of Halal Tourism Development in Lombok Island to Support The Economic Welfare of The Community - Ahsani Taqwiem; Farida Diyan Pertiwi (Publikasi Indonesia, 2021)
Halal tourism has recently begun to be frequently discussed with its enormous economic potential. referring to Crescent Rating data which states that in 2014 Muslims around the world spent around US126.1 billion for tourism expenditure allocation where Indonesia was in the 6th position as the most favorite halal tourist destination in the world. This potential needs to be observed by Indonesia with several favorite tourist attractions that have long been known to the world in this country. Lombok Island as one of the favorite tourist destinations in Indonesia in 2015 has won two awards as the World's Best Halal Tourism Destination and the World's Best Halal Honeymoon Destination where the Governor of West Nusa Tenggara TGM Zainul Majdi has stated his readiness to develop halal tourism in Lombok. with several favorite destinations such as Senggigi Beach, Gili Trawangan, and Mount Rinjani. So in this journal, the author will describe the results of research using a SWOT analysis on the development of halal tourism on the island of Lombok.